2015
DOI: 10.1016/j.jbiosc.2014.10.021
|View full text |Cite|
|
Sign up to set email alerts
|

Production of itaconic acid in Escherichia coli expressing recombinant α-amylase using starch as substrate

Abstract: Several studies on fermentative production of a vinyl monomer itaconic acid from hydrolyzed starch using Aspergillus terreus have been reported. Herein, we report itaconic acid production by Escherichia coli expressing recombinant α-amylase, using soluble starch as its sole carbon source. To express α-amylase in E. coli, we first constructed recombinant plasmids expressing α-amylases by using cell surface display technology derived from two amylolytic bacteria, Bacillus amyloliquefaciens NBRC 15535(T) and Stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…1 In particular, itaconic acid (IA), a promising vinyl monomer that is industrially produced by Aspergillus terreus, 2 has recently been produced in Escherichia coli, [3][4][5][6] Aspergillus niger, [7][8][9] and Synechocystis sp, 10 which were engineered to express the cisaconitate decarboxylase gene (cad) 11 from A. terreus. Vinyl monomers such as IA are promising building blocks for synthetic polymers, because of their radical polymerizability.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1 In particular, itaconic acid (IA), a promising vinyl monomer that is industrially produced by Aspergillus terreus, 2 has recently been produced in Escherichia coli, [3][4][5][6] Aspergillus niger, [7][8][9] and Synechocystis sp, 10 which were engineered to express the cisaconitate decarboxylase gene (cad) 11 from A. terreus. Vinyl monomers such as IA are promising building blocks for synthetic polymers, because of their radical polymerizability.…”
mentioning
confidence: 99%
“…Compared to fungi, E. coli seems to be a more suitable producer of itaconic acid because of its high growth rate; furthermore, gene manipulation of E. coli is easier than that of fungi. 6 Additionally, E. coli has the potential to produce dicarboxylic acids, such as succinic acid, malic acid, and itaconic acid. 6 Li et al demonstrated that E. coli cells containing the cad gene produced 0.08 g/L of IA after overnight growth in Luria-Bertani (LB) medium.…”
mentioning
confidence: 99%
See 3 more Smart Citations